Urinary neutrophil gelatinase-associated lipocalin (uNGAL) levels in patients with nonalcoholic fatty liver disease - (:unkn) unknown (My University, 2012)
Abstract Background/Aims Nonalcoholic fatty liver disease (NAFLD), one of the most common forms of chronic liver disease, is closely associated with obesity and insulin resistance (IR). Adipokines secreted by adipose tissue have recently been implicated in initiating and perpetuating the chronic inflammatory state observed in obesity and NAFLD. Recent studies suggest neutrophil gelatinase-associated lipocalin (NGAL) plays a key role in the pathogenesis of IR. The aims of this study were to determine urinary NGAL levels in patients with ultrasonography proven NAFLD and to correlate these levels with the metabolic profile and fibrosis grade in this population. Methodology Our cohort consisted of 65 consecutive patients undergoing abdominal ultrasonography for clinical suspicion of NAFLD. Patients were subsequently divided into two groups: no steatosis ( n =20) and steatosis ( n =45). The stage of fibrosis was measured using a four-point scale. Urinary NGAL was measured by a specific microparticle enzyme immunoassay. The degree of insulin resistance was determined by the homeostatic model assessment (HOMA). Glucose, insulin, lipid profile, and transaminases were also measured. Results Urinary NGAL levels correlated with body mass index, HOMA, fasting glucose, and insulin levels in patients with steatosis. Moreover, uNGAL levels were higher in patients with steatosis compared to those with no steatosis (49.8 ng/mL and 22.7 ng/mL, respectively) with a statistically significant difference ( p <0.001). A stepwise increase in uNGAL levels from patients without fibrosis (21.7 ng/mL) to patients with cirrhosis (47.4 ng/mL) was noted ( p <0.001). Conclusions Our study demonstrates that in adult patients with NAFLD, uNGAL levels correlate with BMI, insulin resistance, and lipid profiles, and identifies a novel association between uNGAL levels and hepatocellular injury in these patients.